Calcium in the heart: from physiology to disease. Issue 10 (1st October 2014) - Eisner, David
<x xml:space="preserve">Abstract</x> A video of David Eisner giving the 2014 GL Brown Lecture can be viewed here<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>